Pottery in Hellenistic tradition from ancient Bactria: The Kurganzol fortress (Uzbekistan, Central Asia). (October 2018) - Martínez Ferreras, V.; Angourakis, A.; Hein, A.; Gurt Esparraguera, J.M.; Sverchkov, L.M.; Sánchez del Corral, A.
Abstract: Kurganzol is one of the fortresses founded in ancient Bactria during the conquest of Alexander the Great. An archaeometric characterisation was conducted on 20 pottery sherds recovered in the earliest settlement dated to the late-4th BC. The aim is to examine both the composition and variation of the raw materials used and the production technology involved in pottery manufacture. The sampling included plates, cup/bowls, basins, jars, containers, a colander, a bottle or flask and a cooking pot. The analytical program comprised X-ray Fluorescence, X-ray Diffraction, and thin section analysis as well as the study of the geological environment. The analysis of the surface treatment was performed on three sherds through scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDS). The results were compared with an analytical database that includes wares in Hellenistic tradition from coeval sites in the region (i.e. Kampyr Tepe and Termez). The analysis revealed that most of the tableware and common wares analysed correspond to a single local pottery production consisting of a very fine calcareous fabric. Composition and morphological characteristics of these wares enable distinguishing this fabric from other contemporary pottery productions. A regional origin was however assigned for a few wares confirming contacts among different sites. The only cooking pot examined consisted of a calcareous shelltempered fabric which is consistent with a regional technological tradition. Highlights: Different categories of wares from a Hellenistic fortress in Bactria were analysed. The geochemical composition (bodies and surfaces) was compared with coeval wares. Wares from the Seleucid period were mainly local/regional and only a few were imported. Several raw materials were used to form the pastes and the surface coatings. Technological differences are linked to the performance characteristics of the vessels.